An Assessment of Cyber Resilience in the Maritime Domain Using System Dynamics and Analytical Hierarchy Process (AHP) - Putra, I Nengah; Octavian, Amarulla; Susilo, April Kukuh; Santosa, Y N (Transactions on Maritime Science, 2024)
The maritime industry is increasingly dependent on digital technology, making it vulnerable to cyber threats. Every stakeholder is exposed to cybersecurity risks and challenges. This research aims to provide an assessment and simulation model of cyber resilience in the maritime domain, supported by qualitative descriptive statistical methods. This study is also supported by system dynamics and Analytical Hierarchy Process (AHP). The data were obtained from an eight-member expert panel (academics and practitioners) and pertain to the research period January 2022 – February 2023 and the Indonesian Sea area. Research results on global weight revealed the threat (MC-1), vulnerability (MC-2), and technologies (MC-3) sub-criteria as the most important, with the global weight of 0.102 each, followed by the navigation (MO-2), and governance and compliance (CR-6) sub-criteria with the global weight of 0.072 and 0.065, respectively. Maritime cyber resilience evaluation is based on three main criteria. The maritime operation criterion has the highest resilience value, with overall evaluated value of maritime cyber resilience being in the acceptance resilience category level 4, with the value of 3.535 (70.701%). Furthermore, changes in the maritime cyber resilience value in the 2022-2025 period are still at level 4 (acceptance resilience). Maritime cyber resilience is expected to stagnate at its current level 4 in 2023. In the third and fourth year (2024-2025), a downward trend in the maritime cyber resilience value is expected.